Nursing of integrated Traditional Chinese and western medicine for a patient with type 2 diabetes and bullous pemphigoid (1例高龄2型糖尿病合并大疱性类天疱疮患者的中西医结合护理) - ZHANG Jingjin (张京津); LIU Bianyun (刘变云) (Association of Integrative Nursing, 2023)
This paper summarized the treatment and nursing management for a type 2 diabetic patient with bullous pemphigoid. Based on Traditional Chinese Medicine syndrome differentiation, integrative nursing was carried out in various ways including daily care, skin care, dietary care, medication guidance and emotion care. Patient's herpes was rapidly dried, and began to scab as well as fall out. The integrative nursing interventions were effective to improve the healing of herpes and reduce the pain caused by bullous pemphigoid. (本文总结1例高龄2型糖尿病合并大疱性类天疱疮患者的治疗和护理经验。通过中西医结合护理干预, 从生活起居、皮肤护理、饮食调护、用药护理、情志护理等多方面进行辨证施护, 促进患者疱疹迅速干燥、结痂、脱落, 有效改善患者临床症状, 减轻患者痛苦。)